2004
DOI: 10.1007/s00442-004-1496-4
|View full text |Cite
|
Sign up to set email alerts
|

A functional analysis of the crown architecture of tropical forest Psychotria species: do species vary in light capture efficiency and consequently in carbon gain and growth?

Abstract: The crown architectures of 11 Psychotria species native to Barro Colorado Island, Panama were reconstructed from field measurements of leaf and branch geometry with the three-dimensional simulation model Yplant. The objective was to assess the role of species differences in architecture in light capture and carbon gain in their natural understory environment. When species were grouped according to their putative light environment preference, the shade tolerant species were found to have a small but significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
2
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 38 publications
5
78
2
3
Order By: Relevance
“…Similarly, species mean leaf size and self-shading explained most of the variance in light capture of many perennial plants coexisting in Australia temperate forests [11]. Our findings are consistent with results from simulation studies based on virtual plants which found that the higher self-shading was due both to crowding of leaves close to each other and to proximity of leaves to the stem [11,25,33,45,47,50].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similarly, species mean leaf size and self-shading explained most of the variance in light capture of many perennial plants coexisting in Australia temperate forests [11]. Our findings are consistent with results from simulation studies based on virtual plants which found that the higher self-shading was due both to crowding of leaves close to each other and to proximity of leaves to the stem [11,25,33,45,47,50].…”
Section: Discussionsupporting
confidence: 82%
“…The connections between structure and function of plant developmental patterns in relation to light harvesting have received renewed attention during the last years [33]. However, most studies have focused on modeling instead of performing direct measurements of the light really harvested by the plant crown and by the individual leaves within the foliage [27,30,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf display and light capture depend on intra-and interspeciWc responses to light, and the size of the leaves (Falster and Westoby 2003;Pearcy et al 2004Pearcy et al , 2005. Nearly all our knowledge on intraspeciWc metamer responses to light comes from herbaceous (clonal) plants that vary internode length to forage for resources and explore resource-rich patches (Hutchings and de Kroon 1994).…”
mentioning
confidence: 99%
“…The growth depends on the light quantity absorbed in leaves, also on the efficiency of the conversion of light absorbed in biomass and allocation of photoassimilates in tissues . The capture of light by a plant depends on the amount of radiation and the architectural arrangement of leaves within the crown, on a direct leaf orientation to the light sources and on the degree of shading resulting from the overlap of the leaf in a plane orthogonal to the light source (Pearcy et al, 2004).…”
Section: Introductionmentioning
confidence: 99%